Kualitas Pelayanan Kartu Tanda Penduduk Elektronik Pada Kantor Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sigi - Putra, Surya Wisnu Dwi; Nuraisyah; Samsu, M. Kafrawi Al-Kafiah; Sahido, Samsu A. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to examine the quality of Electronic Identity Card (E-KTP) services at the Department of Population and Civil Registration of Sigi Regency. The research focuses on four service quality indicators based on Taliziduhu Ndraha's theory: speed, accuracy, convenience, and fairness. This research uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results of the study show that E-KTP services in Sigi Regency have not been optimal. In terms of speed, the E-KTP issuance process is still slow due to limited facilities such as a lack of recording and printing equipment, as well as network disruptions. Regarding accuracy, services do not meet the standard completion time due to a lack of discipline and preparedness among staff. However, in terms of convenience, the public finds the procedures and requirements for E-KTP services to be accessible and straightforward. Meanwhile, in the aspect of fairness, there are still practices of prioritizing relatives or acquaintances, which leads to public dissatisfaction and a sense of unfairness. The conclusion of this study is that the quality of E-KTP services at the Department of Population and Civil Registration of Sigi Regency still needs improvement, particularly in the aspects of speed, accuracy, and fairness, to ensure more optimal and equitable services.